Historical profile of polychlorinated biphenyls (PCBs) in an alpine glacier - VILLA, SARA; MAGGI, VALTER; Negrelli, C; FINIZIO, ANTONIO; BOLZACCHINI, EZIO; VIGHI, MARCO (INST LEBENSMITTELTECHNOLOGIE ANALYTISCHE CHEMIE, 2001)
An ice-core, drilled on Lys Glacier (Italian Alps), was analysed to determine PCB concentration. Contamination was characterised by low chlorinated congeners (di-, tri- and sometimes tetra- chlorobiphenyls) for all the investigated periods. The historical trend indicates the maximum concentration occurring in the early 1980's. These results are highly correlated to PCB technical mixture burden and physical-chemical properties. The role of temperature on PCB environmental fate is highlighted. High mountains can be considered to be a cold condenser.